Characterization and comparison of novel adjuvants for a prefusion clamped MERS vaccine - O’Donnell, Jake S.; Isaacs, Ariel; Jakob, Virginie; Lebas, Celia; Barnes, James B.; Reading, Patrick C.; Young, Paul R.; Watterson, Daniel; Dubois, Patrice M.; Collin, Nicolas; Chappell, Keith J. (Frontiers in Immunology, 2022)
Various chemical adjuvants are available to augment immune responses to non-replicative, subunit vaccines. Optimized adjuvant selection can ensure that vaccine-induced immune responses protect against the diversity of pathogen-associated infection routes, mechanisms of infectious spread, and pathways of immune evasion. In this study, we compare the immune response of mice to a subunit vaccine of Middle Eastern respiratory syndrome coronavirus (MERS-CoV) spike protein, stabilized in its prefusion conformation by a proprietary molecular clamp (MERS SClamp) alone or formulated with one of six adjuvants: either (i) aluminium hydroxide, (ii) SWE, a squalene-in-water emulsion, (iii) SQ, a squalene-in-water emulsion containing QS21 saponin, (iv) SMQ, a squalene-in-water emulsion containing QS21 and a synthetic toll-like receptor 4 (TLR4) agonist 3D-6-acyl Phosphorylated HexaAcyl Disaccharide (3D6AP); (v) LQ, neutral liposomes containing cholesterol, 1.2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) and QS21, (vi) or LMQ, neutral liposomes containing cholesterol, DOPC, QS21, and 3D6AP. All adjuvanted formulations induced elevated antibody titers which where greatest for QS21-containing formulations. These had elevated neutralization capacity and induced higher frequencies of IFNƔ and IL-2-producing CD4+ and CD8+ T cells. Additionally, LMQ-containing formulations skewed the antibody response towards IgG2b/c isotypes, allowing for antibody-dependent cellular cytotoxicity. This study highlights the utility of side-by-side adjuvant comparisons in vaccine development.